2017
DOI: 10.1017/s1368980017001057
|View full text |Cite
|
Sign up to set email alerts
|

Front-of-package nutrition references are positively associated with food processing

Abstract: The greater frequency of FOP nutrition references on heavily processed foods raises questions about the extent to which discretionary FOP labelling supports public health efforts to promote healthy eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…Results from this study align with findings from other studies that have demonstrated that products with nutrition claims do not always have a more favourable nutritional profile as compared to similar F&Bs without claims [ 31 , 42 ]. The present study is also in line with other research which suggests that nutrition claims are mostly used for food marketing [ 7 , 42 , 43 , 44 ], particularly when claims are used on “less healthy” F&Bs [ 3 , 34 ]. Interestingly, this research also found that the overall proportion of F&Bs considered eligible to carry claims (45%) was similar to studies conducted in Australia and New Zealand (45%) [ 5 ] and another study involving five European countries (43%) [ 10 ], suggesting that the nutritional quality of F&Bs in industrialized countries might be comparable.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results from this study align with findings from other studies that have demonstrated that products with nutrition claims do not always have a more favourable nutritional profile as compared to similar F&Bs without claims [ 31 , 42 ]. The present study is also in line with other research which suggests that nutrition claims are mostly used for food marketing [ 7 , 42 , 43 , 44 ], particularly when claims are used on “less healthy” F&Bs [ 3 , 34 ]. Interestingly, this research also found that the overall proportion of F&Bs considered eligible to carry claims (45%) was similar to studies conducted in Australia and New Zealand (45%) [ 5 ] and another study involving five European countries (43%) [ 10 ], suggesting that the nutritional quality of F&Bs in industrialized countries might be comparable.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have examined the prevalence of nutrition claims on F&Bs labels in Canada [ 4 , 32 , 34 ]. However, since information on the overall nutritional quality of products is not compulsory for products carrying nutrition claims, it is unknown whether F&Bs with nutrition claims are of higher nutritional quality than those without such claims.…”
Section: Introductionmentioning
confidence: 99%
“…Regulations may specify the restriction of ultra-processed foods from marketing to children, or prohibit nutrition and health claims from ultra-processed food products. Research in this special issue identifies that ultra-processed foods currently comprise almost all foods promoted during children's television programmes in Argentina (38) and that these products frequently carry nutrition and health claims in Australia (39) and Canada (40) , which likely leads to health halo effects. Food processing-based classification systems could also be applied in local planning regulations, where these seek to influence the availability or accessibility of foods in local environments.…”
mentioning
confidence: 99%
“…Our study drew on a larger survey of FOP references found on foods and beverages sold in three large grocery stores in Toronto conducted between July 2010 and August 2011 (Sacco et al 2013;Sumanac et al 2013;Christoforou et al 2017). A single store was selected from each of the top three food retailers in Canada (Loblaws, Metro, and Sobeys), representing 71% of the total Canadian retail market share (Canadian Grocer 2009).…”
Section: Data Collectionmentioning
confidence: 99%
“…It has been argued that highly processed products have displaced more traditional items in the diet, in part through the use of aggressive and strategic marketing (Monteiro 2009;Mallarino et al 2013;Scrinis 2016). Manufacturers are able to promote their products through the practice of front-of-package (FOP) nutrition labeling (Health Canada 2010), and such labeling is much more prevalent on highly processed foods than lesser-processed foods sold in Canadian supermarkets (Christoforou et al 2017). Although some of these nutrition references, such as nutrient content claims and those that highlight the health and "functional" benefits of a product, are regulated through compositional criteria (Health Canada 2010; CFIA 2016), other, often more ambiguous, references to nutrition are unregulated.…”
Section: Introductionmentioning
confidence: 99%